Warren Buffett Accounting Book: Reading Financial Statements for Value Investing - Stig Brodersen; Preston Pysh (Pylon Publishing, 2014)
The Warren Buffett Accounting Book is the second volume learning experience to Warren Buffett's Three Favorite Books. This book teaches: 1. Two methods for calculating the intrinsic value of a company 2. What is a discount rate and how does it work 3. Detailed instructions on how to read an income statement, Balance sheet, and cash flow statement 4. How to calculate important ratios to properly value any business
Keywords: Finance; Investments